The great East Asian war and the birth of the Korean nation - Haboush, JaHyun Kim (Columbia University Press, 2016)
"JaHyun Kim Haboush argues that beginning with the outbreak of the Imjin War, when Japan invaded Korea in 1592, a discourse of nation emerged in Chosôn Korea (1392-1910) which continued, in a variety of forms, until the modern era. This is the first book to examine the formation of the Korean nation before the modern era. The Imjin War and the rise of the Manchu were events of monumental importance in East Asian history. The Great East Asian War escalated into a six-year regional war in which the three East Asian countries, Japan, Korea and China, fought either as allies or enemies, with a commitment of large forces, fighting on sea and land. This conflict was by far the largest war known to the world in the sixteenth century. In East Asian memory, it remained unequalled in scale until the Second World War. In Korea the Chosôn dynasty began in 1392 and persisted until 1910, and within this dynasty an idea of nation emerged and circulated. This discourse of nation shifted and intensified after the Manchu invasion in 1636. Haboush shows how this process was a visible, traceable, and documented phenomenon. The idea of a sixteenth century Korean nation is also unfamiliar in Korea. Nationalism for the most part is presented as a preexisting condition in the Imjin War, though 'strengthened' and 'heightened' by the experience. Scholars of the modernist camp subscribe to the historicism of Western historiography. They present the nationhood of Korea as a narrative of transformation, locating its arrival in the modern period, sometime in late 19th or early 20th century, under the auspices of new ideologies and visions from the West"--Provided by publisher.